Evaluating the impact of Benson’s relaxation technique on anxiety and delirium among coronary artery bypass graft surgery patients - Ali Golchoubi; Kheizaran Miri; Saeed Vagheei; Fatemeh Hajiabadi; Mahdi Kahrom; Hamid Reza Behnam Vashani (Journal of Cardiothoracic Surgery)
Abstract Background Anxiety and delirium are prevalent complications in cardiac patients undergoing invasive procedures like coronary artery bypass surgery, with untreated symptoms potentially leading to enduring physical and psychological consequences. Benson’s relaxation technique, a method of attention focusing, has demonstrated efficacy in alleviating various symptoms, although findings are conflicting. Thus, this study aimed to assess the influence of Benson’s relaxation on anxiety and delirium severity in open-heart surgery candidates. Methods Conducted in 2022 at Qaem Hospital in Mashhad, this randomized controlled trial involved 60 patients. The intervention group received Benson’s relaxation training pre-surgery and practiced it twice daily for 72 h post-admission. Standard care was provided to controls. Anxiety and delirium were assessed using standardized scales before and after the intervention. Results The demographic characteristics of both groups were comparable with no significant differences. Benson’s relaxation significantly reduced delirium scores on the first and second days post-surgery (P < 0.001). However, the difference in delirium scores between the groups was not significant on the third day (P = 0.129). While the intervention led to a significant reduction in anxiety within the intervention group, no significant difference in anxiety reduction was observed between the intervention and control groups (P = 0.579). Conclusion Incorporating Benson’s relaxation technique, which showed significant effects in reducing early postoperative delirium, into postoperative care plans for open-heart surgery patients warrants consideration. However, given the lack of a significant effect on anxiety reduction compared to routine care, further research is necessary to evaluate its long-term effectiveness and broader impact on psychological outcomes. Trial Registration This study was registered in the Iranian Registry of Clinical Trials (no. c IRCT20210903052365N1) on 2022-01-28.